The determinants of capital structure in the hotel sector in Portugal - Herdeiro, Inês Alexandra Carvalho (2020)
This research aims to analyze the determinants of the capital structure of companies in the hotel sector in Portugal during a period of economic crisis (2010 to 2014) and a period corresponding to the end of the economic crisis (2015 to 2017). The sample was obtained through the SABI database, selecting the companies belonging to the hotel industry sector. The results indicate that the profitability (as measured by return on assets) negatively influences the companies' indebtedness (or leverage). This behavior may indicate that the companies, under analysis, follow the peking-order theory during this period. The increase in the coefficient of this determinant associated to the increase in the financial autonomy may indicate that the policy of capital structure of the companies changes with the macroeconomic changes.